PEMBERDAYAAN IBU-IBU PKK MELALUI EDUKASI DAN SOSIALISASI BANK SAMPAH BERBASIS MASYARAKAT - Maria Entina Puspita; Dwi Nurrahmawati; Fajar Hidayat; Krisnadwiva Krisnadwiva (Perwira Journal of Community Development, 2026)
This activity aims to provide education and socialization of community-based waste management through waste banks to PKK group mothers in RT 15 RW 5 Kutowinangun Lor, Tingkir, Salatiga City. Education and socialization activities are carried out through presentations by speakers from the Salatiga Waste Bank (BSI), as well as discussions and simulations. The target of this Community Service activity is the PKK group mothers in RT 15 RW 5 Kutowinangun Lor, Tingkir, Salatiga City. Through this education and socialization activity, it is hoped that the PKK group mothers in this RT will be able to manage their waste optimally and begin to be disciplined in selecting and sorting household waste, so that the waste bank program in this RT can be realized for environmentally friendly waste. Waste banks are one of the local government programs in the context of environmentally friendly waste. Through this activity, it is hoped that it can foster awareness and joint commitment for PKK group mothers in selecting and sorting waste with the 3R concept. The follow-up to this education and socialization activity is ongoing assistance so that the assistance participants can truly sort waste independently as an alternative to increasing family economic income.